The Symbolic Meaning of the Cimbingan Tradition in the Chinese Ethnic Community in Turirejo Village, Lawang District, Malang Regency - Lewenussa, Rengganis Aurellia Fika; Hadi, Nur (Universitas Negeri Malang, 2024)
This research describes the Cimbingan tradition which is carried out once a year by visiting the graves of ancestors and cleaning and decorating the graves. Ethnic Chinese still strongly hold the belief to always honor ancestors, so this tradition is still carried out to this day. This research aims to reveal three important focuses, namely: the function and meaning of each equipment used, the worship procession of the Cimbingan tradition, and the symbolic meaning in the Cimbingan tradition. The method used in this research is qualitative descriptif. This research uses data collection techniques in the form of observation, in-depth interviews, and documentation with primary data sources and secondary data sources. Based on the research, it can be concluded that there is a meaning contained in each equipment used such as the meaning of candles and incense which means as a light for the ancestors in the afterlife, besides the offerings of food and drinks which means a form of attention from children to parents. Furthermore, afterlife money and duplicate items made of paper which means a form of fulfilling the needs of ancestors in the afterlife. Furthermore, the five-color paper means a form of description of the ancestors' homes in the afterlife. In addition, there are three stages in the procession of the Cimbingan tradition where there is a preparation stage, a prayer stage, and a closing stage. The meaning in this tradition is a form of filial piety of children to parents, where children still remember and show attention to parents even though parents are gone. Makna Simbolik Tradisi Cimbingan Pada Komunitas Etnis Tionghoa di Desa Turirejo Kecamatan Lawang Kabupaten Malang Penelitian ini mendeskripsikan mengenai tradisi Cimbingan yang dilaksanakan setahun sekalidengan mengunjungi makam para leluhur dan membersihkan serta menghias makam. EtnisTionghoa masih sangat memegang kepercayaan untuk selalu menghormati leluhur, sehinggatradisi ini tetap dilaksanakan sampai saat ini. Penelitian ini bertujuan untuk mengungkapkan tigafokus penting yakni : fungsi dan makna dari setiap perlengkapan yang digunakan, prosesisembayang tradisi Cimbingan, dan makna simbolik yang ada dalam tradisi Cimbingan. Metodeyang digunakan dalam penelitian ini yakni kualitatif deskriptif. Penelitian ini menggunakan teknikpengambilan data berupa observasi, wawancara mendalam, dan dokumentasi dengan sumberdata primer dan sumber data sekunder. Berdasarkan penelitian dapat disimpulkan bahwaterdapat makna yang terkandung didalam setiap perlengkapan yang digunakan seperti maknapada lilin dan dupa yang bermakna sebagai penerang para leluhur di alam baka, selain itupersembahan makanan dan minuman yang bermakna bentuk perhatian anak kepada orangtua.Selanjutnya uang akhirat dan barang duplikat dari kertas yang bermakna sebagai bentukpemenuhan kebutuhan leluhur di alam baka. Selanjutnya kertas lima warna yang bermaknasebagai bentuk gambaran rumah para leluhur di alam baka. Selain itu terdapat tiga tahap dalamprosesi tradisi Cimbingan dimana terdapat tahap persiapan, tahap sembahyang, dan tahappenutupan. Makna yang ada dalam tradisi ini sebagai bentuk bakti anak kepada orangtua, dimanaanak tetap mengingat serta menunjukan perhatian kepada orangtua waluapun orangtua telahtiada.